Vergi Dairesi Yöneticilerinde Empatik Eğilim Düzeylerinin Çalışan Performansı Üzerindeki Etkileri - Yılmaz, Adem (İstanbul Gelişim Üniversitesi Sosyal Bilimler Enstitüsü, 2015)
Empatik beceri insanların yüzyüze olduğu mesleklerde büyük önem taşıyan niteliklerdendir. Vergi dairesi yöneticiliği de çalışanlarla ve halkla sürekli iletişim halinde olan mesleklerden biridir. Bu mesleği icra ederken karşısındaki insanları anlama, onları dinleme, olaylara karşısındakinin açısından bakabilme gibi özellikleri içeren empatik beceri yöneticinin başarısında önemli bir etkendir. Bu çalışma vergi dairesi yöneticilerinin empatik eğilim düzeylerinin ve çalışan performansına etkisinin araştırılması amacıyla yapılmıştır. Bu amaçla ölçek ve mülakat formu İstanbul ilindeki vergi dairesi yöneticilerine bizzat araştırmacı tarafından uygulanmıştır. Empatik becerisi gelişmiş yöneticilerin çalışanları daha iyi güdüleyebildiği ve onların performanslarını artırdığı sonucuna ulaşılmıştır.

Empathic skills are especially important for the occupations that require personal interaction during the business. Tax office management is one of the professions that requires personal interaction with regular communication with employees and the public. Tax office managers come across with wide range of people while performing this profession. Listening and also with using empathy skills are important factors for the success of the managers in terms of ability to evaluate the situations. This research for tax office managers was conducted to investigate the effect of empathic tendencies levels and relationship to employee performance. The questionnaires and interviews from the tax authorities in the province of Istanbul are used for this research. This research results indicate that the employees whom have empathic skills developed administrators can be highly motivated and as a result show better performance.
Inverstigation of Empathic Tendencies in the Tax Department Manager Level
Danışman: Alaattin Fırat
Keywords: Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::SOCIAL SCIENCES::Business and economics